Adsorption of amphiphilic graft copolymers in solvents selective for the grafts on a lyophobic surface: a coarse-grained simulation study. Issue 9 (15th February 2018) - Posel, Zbyšek; Svoboda, Martin; Limpouchová, Zuzana; Lísal, Martin; Procházka, Karel
Abstract : The sorption of graft copolymers on surfaces attractive only for the backbone and its effect on the conformational behavior of adsorbed/desorbed chains in solvents good for the grafts and poor for the backbone was studied by coarse-grained computer simulations. Abstract : The sorption of graft copolymers on surfaces attractive only for the backbone and its effect on the conformational behavior of adsorbed/desorbed chains in solvents good for the grafts and poor for the backbone was studied by coarse-grained computer simulations. It was found that the sorption and conformational behavior are very complex and are results of an intricate interplay of solvent quality (polymer–solvent interactions) and solvent strength (polymer–surface vs. solvent–surface interactions). Increasing grafting density and length of grafts protect the backbone against adsorption, but the behavior is non-trivial. A decrease in solvent quality promotes the adsorption, because it lowers the overall solubility, but the backbone collapses and the probability of backbone–surface contacts decreases, which simultaneously hinders the adsorption. The results of simulations are presented in the form of phase diagrams depicting the decisive features of the conformational and sorption behavior.